Antarctic bacterial natural products: from genomic insights to drug discovery - Medeiros, William; Kralova, Stanislava; Oliveira, Valéria; Ziemert, Nadine; Sehnal, Ludek (Natural product reports, 2025)
Covering: up to the end of 2024Microbial life dominates the extreme continent Antarctica, playing a pivotal role in ecosystem functioning and serving as a reservoir of specialized metabolites known as natural products (NPs). NPs not only contribute to microbial adaptation to harsh conditions but also modulate microbial community structure. Long-term isolation and environmental pressures have shaped the genomes of Antarctic bacteria, suggesting that they also encode unique NPs. Since NPs are also an important source of drugs, we argue that investigating Antarctic bacterial NPs is essential not only for understanding their ecological role and evolution, but also for discovering new chemical structures, biosynthetic mechanisms, and potential new drugs. Yet, despite advances in omics technologies and increased scientific activities in Antarctica, relatively few new bacterial NPs have been discovered. The lack of systematic research activities focused on the exploration of Antarctic bacteria and their NPs constitutes a big problem considering the climate change issue, to which ecosystems in polar regions are the most sensitive areas on the Earth. Here, we highlight the currently available data on Antarctic bacteria, their biosynthetic potential, and the successful NP discoveries, while addressing the challenges in NP research and advocating for systematic, collaborative efforts aligned with the Antarctic Treaty System and the Antarctic Conservation Biogeographic Regions.
Keywords: molekulární struktura; biologické přípravky; Drug Discovery; Genomics; Antarktida; objevování léků; Biological Products; genomika; Bacteria; Antarctic Regions; Molecular Structure